Targeted Codelivery of Doxorubicin and IL-36γ Expression Plasmid for An Optimal Chemo-Gene Combination Therapy against Cancer Lung Metastasis - Chen, Yichao (Nanomedicine, 2018)
Cancer metastasis is the main cause for the high mortality in breast cancer patients. In this work we developed a polymer POEG-st-Pmor for targeted co-delivery of IL-36γ expression plasmid and doxorubicin (Dox) to lung metastasis of breast cancer. The polymer readily formed micelles that were effective in loading Dox and simultaneously forming complexes with IL-36γ plasmid. Interestingly, particles co-loaded with Dox and plasmid was significantly smaller and more stable than the particles loaded with Dox only. Gene transfection in both lungs and s.c. tumors was significantly higher with our polymer compared to PEI. In addition, the Dox+IL-36γ/POEG-st-Pmor could not only bring improved anti-metastatic effect but synergistically enhance the type I immune response by increasing the IFN-γ positive CD4(+) and CD8(+) T cells and simultaneously decreasing the immunosuppressive myeloid-derived suppressor cells in the lung. POEG-st-Pmor may represent a simple and effective delivery system for an optimal chemo-gene combination therapy.